Analysis of street utilization patterns in Makurdi, Benue state Nigeria. - Mngutyo, Irene Doosuur; Alaci, Davidson Ashemi (IJRDO - Journal of Social Science and Humanities Research, 2018)
Streets are public spaces that are meaningful to all people because of lack of restriction. Studies show that conditions, activities and people contribute to the success of public spaces. Also, self-organization potential in activity patterns offers prospect for revitalization of an urban area. This potential is not used hence many African streets appear disorganised giving African urban areas an unplanned look Therefore; this study aims to analyse street utilization patterns and explore the relationship between the pattern of street use and condition of streets in Makurdi .These activity patterns form a data base for revitalization of public space. Three major and minor arterials streets in the nine wards that make up the built up part of Makurdi were purposively selected as units for measurement. A street activity audit was done on streets for activities that can be observed. For activities that cannot be easily observed 4 questionnaires were randomly administered on each of the three streets giving a total of 108 questionnaires. Multivariate statistical tools such as factor analysis and regression will be used to show emerging streets activity patterns and spatial variation among the nine wards.